Digital approach for lip prints analysis in Malaysian Malay population (Klang Valley): photograph on lipstick-cellophane tape technique - Nur Hamizah Md Udin,; Nur Sabrina Sarah Abd Rahman,; Gina Francesca Gabriel,; Noor Hazfalinda Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Personal identification in forensic investigation is not an easy process. Lip print analysis is one of the techniques that can be used to assist in human identification. This study was conducted to investigate the sex based on lip print pattern among Malaysian Malay population in Klang Valley, using photograph on lipstick-cellophane tape technique and the Suzuki and Tsuchihashi classification. A total of 360 subjects (180 males and 180 females) aged 15 and above were included in this study. The lip print was taken by pressing a cellophane tape to the lipstick applied on lip, pasted it onto a plain A4 paper and then photographed using a smart phone camera (OPPO F1). The images were then analysed using Adobe Photoshop software. A lip print image were divided into six sections: upper left, upper middle, upper right, lower right, lower middle and lower left. The Pearson chi-square test showed that there are significant differences between sexes in each section except for the upper middle section. Type V (irregular pattern) was the dominant pattern for the upper left, upper right, lower right and lower left sections (ranging from 71.1% to 86.7% for males and 80.6% to 83.9% for females) while type IV (reticular pattern) was mostly found in upper middle and lower middle section. Malaysian female displayed type V as the dominant lip print pattern in every section (ranging from 39.4% to 83.9%) except upper middle section and for Malaysian male, type V dominated the lip print pattern in all section (ranging from 71.1% to 86.7%) except for the upper and lower middle section. The result of this study can be applied in assisting the human identification for forensic science investigation.